Community Partnerships and Experiential Learning: Investing in the Next Generation of a Diverse, Qualified Public Health Workforce. (December 2021) - Blenner, Sarah R.; Roth, Sarah E.; Manukyan, Rita; Escutia-Calderon, Yareli; Chan-Golston, Alec M.; Owusu, Elaine; Rice, Lindsay N.; Prelip, Michael L.
Annually, the University of California Los Angeles (UCLA) Public Health Scholars Training Program (Program) exposes and engages 35 to 40 undergraduate students, Public Health Scholars, through an 8-week intensive summer training program in public health. Experiential learning through internships is an integral part of the Program, allowing scholars to gain hands-on experience in the field of public health while providing pathways to enter the public health workforce and pursue graduate education. The Program leverages existing strong community partnerships developed through the school's applied practice experiences as well as creates new partnerships. These relationships are mutually beneficial, improve community connections, expand relationships, and develop the school's ability to work with undergraduate students. This article outlines an adapted, evidence-based experiential learning model and develops an evaluation framework to capture the program impact. In the program evaluation, scholars and professional mentors assess the impact of the Program on scholars' intrapersonal, interpersonal, societal, strategic professional, and foundational public health skills. Mentor and peer relationships drive the experiential learning model, supporting the Program to train undergraduate scholars, prepare graduate students to be future mentors once established in the public health workforce, and build the capacity of partner organizations to train a diverse public health workforce. The Program provides a needed opportunity to scholars, most of whom are from underrepresented or underserved backgrounds, to receive in-depth exposure and engagement with public health.